2021
DOI: 10.1187/cbe.20-03-0046
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of University STEM Summer Bridge Program Effectiveness

Abstract: A meta-analysis of university STEM summer bridge programs found that participation had a medium-sized effect on first-year overall GPA ( d = 0.34) and university retention (Odds Ratio OR] = 1.747). Although the analysis reflects the limited available data, it provides much-needed research on programs’ objective effectiveness and guides future program development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…, 2020 ) in introductory-level courses as one way to invoke an asset-based approach to teaching science that creates a more inclusive environment ( Estrada et al. , 2011 , 2016 ; Johnson, 2019 ; MacSwan, 2020 ; Bradford et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2020 ) in introductory-level courses as one way to invoke an asset-based approach to teaching science that creates a more inclusive environment ( Estrada et al. , 2011 , 2016 ; Johnson, 2019 ; MacSwan, 2020 ; Bradford et al. , 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, data from the past few years showed that universities in Aotearoa New Zealand have an increasing number of Pasifika students (University of Auckland, 2021; University of Otago, 2023b). Similarly, universities outside Aotearoa New Zealand may also have increasing enrolment of ethnic minority students, and some have developed initiatives to better prepare them academically (Ashley et al, 2017; Bradford et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These differences can differentially shape how FGWOC experience higher education. In response to these and other contemporary challenges (e.g., diversity in higher education), some colleges and universities have instituted specific programs to recruit and facilitate a smooth transition to college for underrepresented students (i.e., students of color, first-generation, lower-income college students; Bradford et al, 2021; Grace-Odeleye, & Santiago, 2019; Kallison & Stader, 2012). Evidence indicates that the success of these programs depends upon facilitating intentional help-seeking (e.g., meeting with instructors or counselors), making students feel cared for, helping to develop a sense of belonging, and mediating stressful situations, ensuring that interventions are effective and sustaining.…”
Section: Discussionmentioning
confidence: 99%